Serial attention within working memory. - GARAVAN, HUGH PATRICK (Psychonomic Society, 1998)
It is proposed that people are limited to attending to just one ?object? in working memory (WM) at any one time. Consequently, many cognitive tasks, and much of everyday thought, necessitate switches between WM items. The research to be presented measured the time involved in switching attention between objects in WM and sought to elaborate the processes underlying such switches. Two experiments required subjects to maintain two running counts; the order in which the counts were updated necessitated frequent switches between them. Even after intensive practice, a time cost was incurred when updating the two counts in succession relative to updating the same count twice. This time cost was interpreted to be due to a distinct switching mechanism that controls an internal focus of attention large enough for just one object (count) at a time. This internal focus of attention is a subset of WM (Cowan, 1988). Alternative visual and conceptual repetition priming and memory retrieval explanations for the cost involved in switching between items in WM are addressed.
PUBLISHED
Keywords: Psychology